The Role of Insects in Maintaining Ecosystem Balance and Biodiversity - Maramis, Redsway T.D; Rompas, Joice J.I. (Journal of Literacy and Education, 2026)
Insects are the most diverse group of organisms on Earth and play a crucial role in maintaining ecosystem balance. This study aims to examine the role of insects in supporting ecosystem stability and biodiversity. The research employs a qualitative descriptive approach through a literature review of relevant scientific journals, books, and research reports. The results indicate that insects perform essential ecological functions as pollinators, biological control agents, decomposers, and components of food chains. Pollinating insects, such as the honeybee (Apis cerana), play a significant role in enhancing plant reproduction and sustaining ecosystem productivity. In addition, predatory and parasitoid insects contribute to natural pest control, while detritivorous insects support decomposition processes and nutrient cycling. Furthermore, insects serve as important indicators of environmental health. The decline in insect populations due to human activities—including excessive pesticide use, climate change, and habitat destruction—can disrupt ecosystem balance and reduce biodiversity. In conclusion, insects play a vital role in maintaining ecosystem stability. Therefore, conservation efforts and sustainable environmental management are necessary to preserve insect populations and their ecological functions